63 The role of mindfulness in physical dating violence, injuring a partner and psychological dating violence. (19th September 2017) - Ngo, Quyen; Walton, Maureen; Chermack, Stephen; Stein, Sara; Ramirez, Jessica; Cunningham, Rebecca
Abstract : Purpose: Dating violence (DV) is a significant public health concern with serious consequences. Rates of DV are high among youth treated in Emergency Departments (EDs). More research is needed to understand the association between DV aggression (physical DV with and without injury to partner; psychological DV) and its correlates (e.g., mindfulness, technology use, mental health, service utilisation). Methods: Participants included emerging adults (EAs; 18–25 years) treated in an urban ED who completed a self-administered computer survey. Multinomial logistic regressions were conducted for physical DV (PDV) with/without injury and PDV with/without psychological DV (PsDV), and included mindfulness, alcohol consumption, cell phone use, anxiety and demographics. Results: The sample included 746 EAs (37% Female, 61% African American, average age 21.5 years). Compared to those with no PDV, those with PDV/no injury had lower mindfulness (OR=0.97, 95% CI:0.95–0.99), more alcohol OR=1.14, 95% CI:1.06–1.23), more anxiety OR=1.06, 95% CI:1.02–1.11), and more cell phone use (OR=2.25, 95% CI:1.06–4.77). Participants with PDV/injury and those with PDV/PsDV had lower mindfulness (OR=0.95, 95%, CI:0.92–0.98; OR=0.96, 95% CI:0.94–0.99), more alcohol (OR=1.15, 95% CI:1.05–1.27; OR=1.18, 95% CI:1.09–1.29), and more anxiety (OR=1.08, 95% CI:1.02–1.14; OR=1.10, 95% CI:1.05–1.16). Participants reporting PDV/no PsDV reported lower mindfulness (OR=0.93, 95% CI:0.89–0.98) and more alcohol consumption (OR=1.19, 95% CI:1.04–1.38). Those with DV were no more likely to have received treatment then those without. Conclusions: Mindfulness, alcohol, and anxiety are significant factors in PDV regardless of partner injury or concurrent PsDV. Those reporting DV are just as likely to use cell phones as those with no DV. They are also no more likely to have received mental health or substance use treatment. Contributions: This research suggests: 1) potential for mindfulness-based interventions to reduce DV; 2) technology-enhanced interventions are a viable approach; 3) interventions are needed because perpetrators are no more likely to have received treatment.